Kreowanie dyskursu publicznego w Polsce – rola mediów krytycznych wobec Prawa i Sprawiedliwości - Panicz, Urszula (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
The aim of the article is to solve the problem, whether the media is responsible for the decline in the quality of a public debate. The comparison of media transmission has led to the conclusion that media was especially critically oriented towards PiS what brought about its politicization. The idea of Marcin Król is used in order to describe the reasons of media manipulation. The measure that could lead to the end of such conflicts has been suggested. That is deliberative democracy.